Fractional factorial design optimization of nontraditional completion fluid for perforation with underbalance - Khalil, M.; Jan, B.M.; Abdul Raman, Abdul Aziz (2010)
Optimal well performance is always associated with the creation of a clean and undamaged connection between wellbore and reservoir. However, it is apparent that the use of shaped-charge perforating tends to produce perforation-induced formation damage. This damage impairs fluid flow and decreases well productivity. To minimize and eliminate this damage, underbalance perforating should be considered. Underbalance perforating has been considered as one of the best means of providing a transient surge flow for tunnel cleanup. This paper introduces the formulation of super lightweight completion to achieve underbalance condition. The formulation was optimized using fractional factorial design. The result indicates that the experimental data and model predictions agreed well. The optimum formulation condition is able to produce a stable fluid with minimum and acceptable density and viscosity